Experimental investigation of different failure modes of jalousie type window frames and determination of threshold capacity against static wind pressure - Carandang, Alvin A. Jr
Glazing components of a building envelope refer to windows, doors, or any portions made of glass that permit light and provide a view of the outside of a building. However, with the presence of severe winds in particular areas, glazing components are prone to failure. These components usually experience glass breakage or failure of anchorage and frames. This is mainly due to wind-induced pressure, windborne debris, water intrusion, or any combination where the capacity of the component is exceeded. This study experimentally investigated the capacity of typical jalousie type window frames against simulated static wind pressures. Clients prefer these types of windows because they are economical and easy to repair. The configuration of the samples used in this study was patterned after DPWH school buildings located in typhoon-prone areas in the Philippines. Their configuration had slight differences in opening height and width of a window panel due to testing constraints. The static wind pressures were simulated by a 15-kPa air blower that drew out air inside a 2.4 m x 2.4m x 0.4m air chamber to create a pressure difference across the samples. The window specimen was placed on top of the air chamber such that one side of the window would be experiencing a negative or suction pressure. To hold the test sample in place on top of the air chamber, an attachment system was designed and developed. To fulfill the intended simulation, the test specimen including the attachment system was sealed by using polyethylene sheets and duct tapes to prevent significant air leakage. The set up made use of a pressure sensor (BMP 180) to measure the pressure inside the air chamber from the start of the experiment to the time of failure. Pressure versus time curves were then post processed from the raw data to determine the failure pressure for each test. Furthermore, deflection-time and deflection-pressure curves were developed in the study.A total of five air chamber tests were performed where four of which experienced pull-through failures of the standard aluminium casing and one of which experienced breakage of glass blades. In addition, 5 four point bending tests were performed with the use of UTM to estimate the capacity of the glass blades. By considering only the failure pressures of pull-through, the mean capacity of typical jalousie window frames is 4.218 kPa with a coefficient of variation of 0.23. This variation accounts for the differences in the condition of materials used such as fabrication, handling, and installation. It was then compared to some assumptions made in developing fragility curves of school buildings in the Philippines. Previous studies used ASTM 1300 to estimate the threshold value of glass blades used in such window types, taking into consideration of glass breakage only, not the failure of the frames. The threshold capacity obtained from this study will be useful for developing fragility and vulnerability curves of buildings in future studies. In addition, the results will help improve the conventional ways of installing such window types in the Philippines.